Impacts of Antarctic Sea Ice, AMV and IPO on Extratropical Southern Hemisphere Climate: A Modeling Study - Zhu, Zhu; Liu, Jiping; Song, Mirong; Wang, Shaoyin; Hu, Yongyun (Frontiers in Earth Science, 2021)
Some studies have discussed potential influences of Antarctic sea ice anomalies, Atlantic Multi-decadal Variability (AMV), and Interdecadal Pacific Oscillation (IPO) on the Southern Hemisphere (SH) climate, individually. However, it is not clear how different combinations of them influence the extratropical SH climate. Here we select three different combinations of strong anomalies in Antarctic sea ice (SI), AMV and/or IPO identified from observations, and investigate their influence on the winter extratropical SH climate using the Community Atmosphere Model. The model results show that atmospheric responses vary with different combinations. When both SI and AMV are in strong positive polarity (SI+AMV), the polar jet shifts equatorward while the subtropical jet shifts poleward, the amplitude of zonal wave number 1 is reduced in high-latitudes with minimal changes in wave number 2, and a north-south circulation dipole occurs in both the Atlantic and Pacific. Different from SI+AMV, when SI is in strong positive polarity and IPO is in strong negative polarity (SI-IPO), the reduction of wave number 1 is dramatically increased, accompanied by remarkably increased wave number 2. The north-south circulation dipole only occurs in the Pacific and is confined to the central and eastern Pacific, whereas the Atlantic is dominated by anomalously anticyclonic circulation. Together, SI+AMV-IPO leads to the largest reduction of wave number 1 in high-latitudes and subtropics, the strongest north-south circulation dipole in the Pacific as well as the Amundsen Sea Low. As a result, the three combinations produce different patterns of surface temperature and precipitation anomalies over Antarctica, Australia and South America.